Planetary nebula luminosity function distances for 19 galaxies observed by PHANGS-MUSE - Scheuermann, Fabian; Kreckel, Kathryn; Anand, Gagandeep S; Blanc, Guillermo A; Congiu, Enrico; Santoro, Francesco; Van Dyk, Schuyler D; Barnes, Ashley T; Bigiel, Frank; Glover, Simon; Groves, Brent; Klessen, Ralf S.; et al. (Monthly notices of the Royal Astronomical Society, 2022)
We provide new planetary nebula luminosity function (pnlf) distances to 19 nearby spiral galaxies that were observed with VLT/MUSE by the PHANGS collaboration. Emission line ratios are used to separate planetary nebulae (pne) from other bright $[\mathrm{O}\, {\small III}]$ emitting sources like compact supernovae remnants (snrs) or H ii regions. While many studies have used narrowband imaging for this purpose, the detailed spectral line information provided by integral field unit (ifu) spectroscopy grants a more robust way of categorizing different $[\mathrm{O}\, {\small III}]$ emitters. We investigate the effects of snr contamination on the pnlf and find that we would fail to classify all objects correctly, when limited to the same data narrowband imaging provides. However, the few misclassified objects usually do not fall on the bright end of the luminosity function, and only in three cases does the distance change by more than 1σ. We find generally good agreement with literature values from other methods. Using metallicity constraints that have also been derived from the same ifu data, we revisit the pnlf zero-point calibration. Over a range of 8.34 < 12 + log (O/H) < 8.59, our sample is consistent with a constant zero-point and yields a value of $M^{*} = -4.542^{+0.103}_{-0.059}\, \mathrm{mag}$, within 1σ of other literature values. MUSE pushes the limits of pnlf studies and makes galaxies beyond ${20}{\, \mathrm{Mpc}}$ accessible for this kind of analysis. This approach to the pnlf shows great promise for leveraging existing archival ifu data on nearby galaxies.